EDUCATION OF ORTHOPEDIST-TRAUMATOLOGIST ORDINATORS ON THE BASES OF INTERNSHIP. WAYS OF REALIZATION - Сулима, В. С.; Андрейчин, В. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Nowadays is needed training experienced orthopedist-traumatologists in order to improve the qualified medical care according as one of the way of further development of the medical care. Professionally oriented training of ordinators involves the development of the motivation for theoretical, practical and scientific self-education. The training of subject "Traumatology and Orthopaedics" in the bases of full-time and distance training should be realized by the way of professional combination of and scientific, theoretical and practical elements of training under supervision of head of department, professors and experienced manager of distance training base that allows optimally organize, control and coordinate the practical training of future specialists.